'Filling the mattress': Trust development in the governance of infrastructure megaprojects. Issue 4 (May 2021) - Ruijter, Hans; van Marrewijk, Alfons; Veenswijk, Marcel; Merkus, Sander
Highlights: Unique autoethnography of a megaproject leader/researcher. An auto-ethnographic study providing in-depth insights in the process of trust development. The study focuses on the role of workshops in the stages of trust development between public and private partners. Trust in partnerships is developed through a laborious process of organizing workshops. A balanced reciprocal relationship is needed for long term collaboration of project partners. Abstract: The development of trust is a major challenge for the governance of public private infrastructure megaprojects. Contractual pre-arrangements should provide a blueprint for collaborative behavior and trust development but the characters of megaprojects challenge such arrangements. This longitudinal study explores practices of trust development in the collaboration of commissioner and contractor consortia in the Dutch road infrastructure megaproject 'Schiphol, Amsterdam and Almere' (SAA). The findings show that six different types of workshops have been used to intervene in the collaboration of project partners in order to develop trust. The study contributes to the debate on governance in megaprojects showing how governance arrangement are enacted in the daily practice in megaprojects. To buffer the potential loss of trust through conflicts, project partners negotiated for a balanced reciprocal relationship, which is the simultaneous exchange of equivalent resources without delay.